Outcome of Calcaneoplasty in Insertional Achilles Tendinopathy - Lim, SM (Malaysian Orthopaedic Association, 2012)
ABSTRACT: Background: Insertional Achilles tendinopathy may be associated with Haglund’s deformity and result in chronic pain. It is usually refractory to conservative management. The aim of this study was to assess the outcome of calcaneoplasty performed in our hospital. Methods: Eight patients were prospectively evaluated pre- and postoperatively using the American Orthopaedic Foot and Ankle Society (AOFAS) Hindfoot Score, Visual Analogue Scale (VAS) and Short Form (SF) 36, as well as satisfaction rate. Average follow-up duration was 12.4 months. Results: The mean pre and post-operative AOFAS scores were significantly improved at three and six months. SF 36 improved in most parameters. The postoperative VAS score improved significantly and was 0 at 2 years. The procedure was rated as good to excellent by seven of the subjects. Conclusion: We recommend calcaneoplasty for the treatment of insertional Achilles tendinopathy. KEY WORDS: Calcaneoplasty, Insertional Achilles tendinopathy, Haglund’s deformity